Total syntheses of the archazolids: an emerging class of novel anticancer drugs - Scheeff, Stephan; Menche, Dirk (Beilstein Journal of Organic Chemistry, 2017)
V-ATPase has recently emerged as a promising novel anticancer target based on extensive in vitro and in vivo studies with the archazolids, complex polyketide macrolides which present the most potent V-ATPase inhibitors known to date, rendering these macrolides important lead structures for the development of novel anticancer agents. The limited natural supply of these metabolites from their myxobacterial source renders total synthesis of vital importance for the further preclinical development. This review describes in detail the various tactics and strategies employed so far in archazolid syntheses that culminated in three total syntheses and discusses the future synthetic challenges that have to be addressed.
Keywords: anticancer agent; medicinal chemistry polyketides; synthetic methodology; total synthesis